Civil society participation in international governance: the UN and the WTO compared - Jens Steffek; Claudia Kissling (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
Civil society participation has become a buzzword in the debate about the legitimacy and accountability of international governance. Many organizations, prominently among them the World Trade Organization (WTO), have come under considerable pressure to open up their policy-making process towards non-state actors. Although the WTO has become more transparent in recent years, direct stakeholder access to its policy making is still denied. This situation is often contrasted with that at the United Nations (UN), where there is (allegedly) much more formally regulated and more substantial participation of civil society. In this paper, we compare the patterns of participation in these two organizations and seek to identify some common dynamics. We present a general framework for analysis based on a model of the policy cycle that allows us to distinguish 'push' and 'pull' factors that determine cooperation in different phases of policy making. In our empirical study, we find that in the WTO, there are few incentives for the organization itself to pull civil society actors into its policy-making process. Agendasetting is the task of governments; research and analysis is delivered by the Secretariat; compliance control is undertaken jointly by the organization and its members. To push the door to trade policy making open, civil society can only rely on public shaming, that is, threatening to undermine the organization's legitimacy as it violates widely accepted standards of good governance. In the UN system, there is in fact more cooperation, but it remains largely limited to the policy phases of agenda-setting, research and analysis and compliance control. Quite like the WTO, the UN protects an intergovernmental core of policy making in which cooperation with civil society remains at the discretion of state parties. Evidence for this are informal and ad hoc ways of collaboration and a lack of participatory rights for non-state actors in the Security Council and the General Assembly. We conclude that studying civil society participation in international public organizations through the lens of the policy cycle can give us a fine-grained picture of cooperative arrangements and enables us to identify potentials for cooperation as well as exclusion. Yet, we also observed two other factors at work that were not really grasped by the model of the policy cycle. First, the institutional culture of organizations can be more or less amenable to civil society. Second, organizations are susceptible to campaigns for 'good governance' that invoke standards of due process and may open the door to nonstate actors.
Keywords: 320; Bürgerbeteiligung; Internationale Organisation; Welt